2008
DOI: 10.1111/j.1540-5907.2008.00329.x
|View full text |Cite
|
Sign up to set email alerts
|

The Context Matters: The Effects of Single‐Member versus At‐Large Districts on City Council Diversity

Abstract: Scholars continue to debate the degree to which electoral institutions matter for representation. The literature predicts that minorities benefit from districts while women benefit from at-large elections. The mechanisms by which institutions affect the ability of traditionally underrepresented groups to win seats have been understudied. Using an analysis of over 7,000 cities and interviews with city councilors, we find that compared to at-large systems, district systems can increase diversity only when underr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
139
0
6

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 184 publications
(147 citation statements)
references
References 55 publications
2
139
0
6
Order By: Relevance
“…The vast majority of research attempting to answer this question has focused on the indirect effect of the VRA on black representation. In particular, building upon the large body of research demonstrating an association between single-member districts and minority representation (Bullock and MacManus 1993;Engstrom and McDonald 1981;Karnig and Welch 1982;Marschall, Ruhil and Shah 2010;Meier and England 1984;Trounstine and Valdini 2008), scholars have long hypothesized that electoral changes in covered jurisdictions would lead to increases in minority representation. Specifically, single-member districts (SMD) are argued to concentrate blacks into compact electoral districts, reducing their reliance upon other groups in the electorate and increasing their capacity to elect black candidates to legislative office.…”
Section: How? Explaining Black Gains In Council Representationmentioning
confidence: 99%
“…The vast majority of research attempting to answer this question has focused on the indirect effect of the VRA on black representation. In particular, building upon the large body of research demonstrating an association between single-member districts and minority representation (Bullock and MacManus 1993;Engstrom and McDonald 1981;Karnig and Welch 1982;Marschall, Ruhil and Shah 2010;Meier and England 1984;Trounstine and Valdini 2008), scholars have long hypothesized that electoral changes in covered jurisdictions would lead to increases in minority representation. Specifically, single-member districts (SMD) are argued to concentrate blacks into compact electoral districts, reducing their reliance upon other groups in the electorate and increasing their capacity to elect black candidates to legislative office.…”
Section: How? Explaining Black Gains In Council Representationmentioning
confidence: 99%
“…The presence of black or Hispanic council members is related to council size and election method (Alozie and Manganaro 1993a;Brouthers and McClure 1985). Trounstine and Valdini (2008) however, find that council size does not matter nearly as much as election method for minority representation. Whereas Hispanics require larger councils to secure a seat, election method rather than council size has a greater effect on minority representation.…”
Section: Council Size and Election Methodsmentioning
confidence: 88%
“…When taking race/ethnicity and gender into account, only black men and white women seem to be aided by government structure (Trounstine and Valdini 2008). Both groups are only aided insomuch as they gain a presence on councils and not in terms of their proportionate share of councils.…”
Section: Council Size and Election Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, most studies in the Czech Republic confirmed that municipality size has a significant influence, for instance, on voter turnout as one of the indicators of citizen participation in local politics (Kostelecký, 2005;Ryšavý and Bernard, 2013). In spite of the existence of contrary results by Magin (2013), the assumption that larger municipalities are more promising to women's representation was confirmed by most of the few studies analysing local elections (Welch and Karnig, 1979;Bullock and MacManus, 1991;Trounstine and Valdini, 2008;Smith, Reingold and Owens, 2012). Similarly, positive effect on women's representation is usually associated with the role of education and employment.…”
Section: Determinants Of Women's Representation At the Local Levelmentioning
confidence: 86%